Description of Chemical Multirepresentation on Acid-Base Material in Merdeka Curriculum Chemistry Textbooks - Septiani, Anggi; Aini, Faizah Qurrata (FKIP - Universitas Riau, 2025)
The concept of acid-base is an essential and complex material because it is abstract. Textbooks play an important role in helping students' understanding through the use of representations to describe chemical phenomena that can make it easier for students to understand the material, especially on difficult material. However, the representations in the merdeka curriculum chemistry textbooks are generally sourced from websites or platforms that cannot be trusted. This study aims to analyze multirepresentation on acid-base material in the chemistry textbooks of the merdeka curriculum, using the method developed by Gkitzia. The data source in this study is the merdeka curriculum chemistry textbook which is generally used in SMA / MA Padang City. The results of this study show that textbook A and textbook B are dominant in the type of symbolic representation 64% and 50% (C1), book A and book B are generally explicit (C2), the relatedness to text, in book A is generally completely related and linked, book B is completely related and unlinked (C3), in book A and book B there is generally no caption (C4), the relationship between representations in book B is generally not quite related (C5).